Population dynamics and regeneration of Shorea roxburghii, a threatened timber species in Southern region, Viet Nam (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Bao TQ, Viet LH, Hai NH, Tuan NT, Cuong LV. 2021. Population dynamics and regeneration of Shorea roxburghii, a threatened timber species in Southern region, Viet Nam. Biodiversitas 22: 5649-5656. Despite its wide distribution in South and Southeast Asia, Shorea roxburghii G. Don is classified as Vulnerable in the IUCN Red List of Threatened Species due to over-exploitation for its valuable timber. This study aims to investigate the population dynamics and regeneration of S. roxburghii in southeastern Vietnam, serving for conservation and sustainable development plan. Six plots of 2,500 m2 each (50 m × 50 m) were established at two forest conditions: i) forest with standing volume > 200 m3/ha (SV>200), and ii) < 200 m3/ha (SV200 than that at the forest stand with SV200 for the pool of S. roxburghii compared to that in SV